Pengaruh Wet Cupping terhadap Peningkatan Kadar Hemoglobin - Ibrahim Edy Sapada; Wita Asmalinda (Jurnal Kesehatan, 2019)
Efforts to increase hemoglobin are by exercise and physical activity, nutritions food, and wet cupping. Some mechanisms that are thought to underlie the work pathophysiology of Wet cupping include Wet cupping which has the main effect through the pathways of the regulatory system of coagulation such as decreasing blood elements, increasing blood flow and organ oxygenation. The aims of this research to know the effect of Wet cupping on increased hemoglobin level. This study was an experimental clinical trial with the comparison (pretest and posttest with control group design). The research is done at the Clinical Cupping Ibnu Sina Palembang for 30 days. The sample in this study were some adult women who meet the criteria of inclusion and exclusion. A sample size of 52 people. Measurement parameter had an increase of hemoglobin. which included a homogeneity test sample using Kolmogorov-simov test, description analysis to know to mean value and standard deviation. There were significantly increased in the number of hemoglobin. Wet cupping affects the increase in hemoglobin levels.